Functional Outcome of Arthroscopic Anterior Cruciate Ligament Reconstruction Using Hamstring Autograft - Yadav, Deependra; Babu Bhandari, Pratap; Khanal, Sudeep; Bhattachan, Sijan; Bista, Kishor; Gurung, Subash; Khanal, Kiran; Sherchan, Binod (Nepal Orthopaedic Association Journal, 2024)
Introduction: There are many autograft and allograft options available for ACL reconstruction. The use of hamstring autograft has become popular nowadays due to ease of harvest and less donor site morbidity. We have routinely been doing arthroscopic ACLR with hamstring autograft in our center. This study aims to evaluate the functional outcome of arthroscopic ACLR with hamstring autograft.Method: This prospective study was done in National Trauma Center, Bir Hospital, Kathmandu from June 2019 to June 2020. Arthroscopic ACL reconstruction was done using hamstring autograft fixed with endobutton on the femoral side and bioabsorbable screw on the tibial side. Functional outcome was measured with IKDC score, Lysholm score, and return to pre-injury status.Results: A total of 28 cases were included in the study. At the final follow-up, mild to moderate pain was present in seven patients (25%). Nine patients had numbness around the knee. Seven cases (25%) had grade I laxity with a hard endpoint. 82% of the patients had excellent to good functional outcomes, and 93% of cases had normal to near normal IKDC scores. 79% of patients returned to pre-injury level.Conclusion: Arthroscopic ACL reconstruction with hamstring auto-graft has good to excellent functional outcomes, with the majority of patients returning to pre-injury status following compliance with physiotherapy.